BREEDING, AGE AND GROWTH OF THE FRESHWATER SHARK WALLAGO ATTU (BLOCH AND SCHNEIDER) FROM THE DHIR BEEL OF THE BRAHMAPUTRA BASIN, ASSAM, INDIA. - GOSWAMI, P. K.; DEVARAJ, M. (Journal of Indian Fisheries Association, 2015)
The Dhir becl, one of the major live becls of the Brahmaputra basin, Assam, has an area of 689 ha and is situated in Dhubli district of Assam. The dominance of freshÂ·water shari<., Wal/ago attu (8.10%) in the becl is a striking feature. Restricted breeding of W. attu . once a year from June to Septemebr Â·was obsen’ed. The. mean obset’\’ed length was 37.5, 65.0, 84.5 and 99.0 em in the 6th, 12th, 18th and 24th months of age respectively. The length growth coefficient (K), the asymptotic len!,Jfh (Loc ), and the arbitrary origin of the growth curve (to), for W. attu were estimated to be 0.054484 per month, 136.16 em and 0.0355 month respectively. The calculated life span (Toe) of the fish is 123.86 months (about 10 years). The weight growth parameters were estimated where the monthly growth coefficient (K), the as:vmptotic (Woc) and the arbitrary origin of’ the growth cun’e (to) were found to be 0.0743 j>er month, 7636,92 gram and 0.431908 month respectively. The length - weight relationship follows the cube law